Determinaç\~ao dos superávits do governo central brasileiro: Influência da política monetária na ótica de regress\~oes de limiar - Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper studies the determination of the surpluses of the Brazilian central government. For quarterly data from 1996 through 2011, the empirical strategy included: i) structural break models and nonlinear estimates on the level of public debt, to handle the inertia after 1999, for high levels of indebtedness; ii) threshold regressions, which account for the influence of monetary policy in the fiscal stance; and iii) a comparison of the estimates by the means of forecast statistics. The following indications are noteworthy: i) there is a tendency to reduce de surpluses as a proportion of GDP, due to the persistent decline in the debt-to-GDP ratio; ii) the CPI inflation and the interest outlays represent state variables in the determination of the surpluses; and iii) the scenario for fiscal policy depends on how those variables will behave after the cuts in the Selic rate in the recent cycle of monetary expansion.
Keywords: E63; H62; H68; 330; primary surpluses; net public debt; inflation rate; interest accruals; threshold regressions; Öffentliche Schulden; Inflation; Strukturbruch; Regression; Geldpolitik; Brasilien